2019
DOI: 10.1016/j.cherd.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium theory analysis of thermal regeneration of a humid adsorption column: Selection of optimal hot purge gas temperature

Abstract: A Thermal Swing Adsorption (TSA) process has been widely commercialised for its application to air drying. In designing an air-drying TSA, zeolite 13X is chosen as a desiccant when required to produce a very low dew point dry air due to its highly nonlinear, favourable isotherm. It is essential to make use of an external hot purge gas in producing such an extremely low dew point dry air, as the column has to be regenerated thoroughly for the next adsorption step. In case of the externally heated TSA, usage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, further examination and comparison of experimental breakthrough curves with our model predictions revealed that this assumption was not entirely accurate in this study. Moreover, in the capillary condensation region, the adsorption and desorption breakthrough behaviors differ from each other. This is due to the fact that in this region, the pores of the adsorbent fill with water molecules, which leads to a decrease in the available adsorption sites. As a result, the adsorption capacity of the adsorbent decreases while the desorption capacity increases.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, further examination and comparison of experimental breakthrough curves with our model predictions revealed that this assumption was not entirely accurate in this study. Moreover, in the capillary condensation region, the adsorption and desorption breakthrough behaviors differ from each other. This is due to the fact that in this region, the pores of the adsorbent fill with water molecules, which leads to a decrease in the available adsorption sites. As a result, the adsorption capacity of the adsorbent decreases while the desorption capacity increases.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Kuznyk et al [47] took data from Bales [43] and fit a model based on the Langmuir isotherm, a linear contribution in the transition zone and capillary condensation. Ahn [48] uses experimental data from Wang [46] and combines the FHH and Aranovich-Donohue (AD) models. In the works cited, a good agreement is found between experimental and simulated data.…”
Section: Equilibrium Model and Isosteric Heat Of Adsorptionmentioning
confidence: 99%
“…To pursue our model, we have selected the simulated isotherms from Ahn [48], which are also available in Figure 3. Simulated data agrees with the fitted experimental data from Wang [46].…”
Section: Equilibrium Model and Isosteric Heat Of Adsorptionmentioning
confidence: 99%
“…Equilibrium Theory has since been developed further to analyse various adsorption systems, e.g. a PSA system with linear isotherm 27,28 , a PSA system with nonlinear isotherms 29,30 , effect of incomplete purge in a PSA system 31 , adiabatic temperature swing adsorption system 32 , etc.…”
Section: Process Description Of Adsorptive Beer Dealcoholisation Process 18mentioning
confidence: 99%
“…While the process performances are affected by both adsorption equilibrium and kinetics, analysis of an adsorption process can be simplified greatly by equilibrium theory in which adsorption kinetic effects is neglected . The equilibrium theory has since been developed further to analyze various adsorption systems, e.g., a PSA system with linear isotherms , and a PSA system with non-linear isotherms, , the effect of incomplete purging in a PSA system, an adiabatic temperature swing adsorption system, etc.…”
Section: Design Of the Ethanol Recovery Vsa System By The Equilibrium...mentioning
confidence: 99%